On the regularity criterion on one velocity component for the micropolar fluid equations - Agarwal, Ravi P.; Alghamdi, Ahmad M.; Gala, Sadek; Ragusa, Maria Alessandra (Mathematical Modelling and Analysis, 2023)
In this paper, we establish a regularity criterion for micropolar fluid flows in terms of the one component of the velocity in critical Morrey-Campanato space. More precisely, we show that if where then the weak solution (u,w) is regular.